A study of pressure drop in reticulated ceramic sponges using direct pore level simulation. (22nd June 2016) - Parthasarathy, P.; Habisreuther, P.; Zarzalis, N.
Abstract: New values for the viscous and inertial coefficients of the Ergun equation to calculate the pressure drop within open cell ceramic sponges made of alumina and silicon infiltrated silicon carbide (SiSiC) are provided based on the direct pore level simulations (DPLS) results. The fluid flow through ceramic structures of different cell densities and porosities are simulated using standard Navier–Stokes equation without any simplification. The computational grid data are reconstructed from three-dimensional computer tomography scans of different reticulated porous media. Influence of tortuosity on the pressure drop is included in a Ergun equation based pressure drop correlation. The new correlation is dependent on the sponge properties such as, cell diameter, specific surface area and flow tortuosity. Abstract : Highlights: The direct pore level numerical simulations are performed to calculate the pressure drop within reticulated porous ceramics. New values for the viscous and inertial coefficients of the Ergun equation to calculate the pressure drop within open cell ceramic sponges are proposed. Flow tortuosity values are calculated and an attempt is made to study the influence on pressure drop.